1H NMR-based metabolomics reveals neurochemical alterations in the brain of adolescent rats following acute methylphenidate administration. (September 2017) - Quansah, Emmanuel; Ruiz-Rodado, Victor; Grootveld, Martin; Probert, Fay; Zetterström, Tyra S.C.
Abstract: The psychostimulant methylphenidate (MPH) is increasingly used in the treatment of attention deficit hyperactivity disorder (ADHD). While there is little evidence for common brain pathology in ADHD, some studies suggest a right hemisphere dysfunction among people diagnosed with the condition. However, in spite of the high usage of MPH in children and adolescents, its mechanism of action is poorly understood. Given that MPH blocks the neuronal transporters for dopamine and noradrenaline, most research into the effects of MPH on the brain has largely focused on these two monoamine neurotransmitter systems. Interestingly, recent studies have demonstrated metabolic changes in the brain of ADHD patients, but the impact of MPH on endogenous brain metabolites remains unclear. In this study, a proton nuclear magnetic resonance ( 1 H NMR)-based metabolomics approach was employed to investigate the effects of MPH on brain biomolecules. Adolescent male Sprague Dawley rats were injected intraperitoneally with MPH (5.0 mg/kg) or saline (1.0 ml/kg), and cerebral extracts from the left and right hemispheres were analysed. A total of 22 variables (representing 13 distinct metabolites) were significantly increased in the MPH-treated samples relative to the saline-treated controls. The upregulated metabolites included: amino acid neurotransmitters such as GABA, glutamate and aspartate; large neutral amino acids (LNAA), including the aromatic amino acids (AAA) tyrosine and phenylalanine, both of which are involved in the metabolism of dopamine and noradrenaline; and metabolites associated with energy and cell membrane dynamics, such as creatine and myo -inositol. No significant differences in metabolite concentrations were found between the left and right cerebral hemispheres. These findings provide new insights into the mechanisms of action of the anti-ADHD drug MPH. Highlights: The effect of MPH on endogenous brain metabolites was investigated. Acute MPH treatment increased the levels of a number of cerebral metabolites, including amino acid transmitters (e.g. GABA and glutamate) and aromatic amino acids (e.g. tyrosine and phenylalanine). The upregulated metabolites may elevate both cerebral excitatory and inhibitory neurotransmission processes.